Histological evaluation of thyroid lesions using a scanning acoustic microscope - Miura K; Mineta H (Dove Medical Press, 2014)
Katsutoshi Miura,1 Hiroyuki Mineta2 1Department of Health Science, Pathology, and Anatomy, 2Department of Otorhinolaryngology, Hamamatsu University School of Medicine, Hamamatsu, Japan Purpose: A scanning acoustic microscope (SAM) uses an ultrasound to image an object by plotting the speed-of-sound (SOS) through tissues on screen. Because hard tissues result in great SOS, SAM can provide data on the tissue elasticity. This paper investigated the utility of SAM in evaluating thyroid lesions. Methods: Formalin-fixed, paraffin sections were scanned with a 120 MHz transducer. SOS through each area was calculated and plotted on the screen to provide histological images, and SOS of each lesion was compared and statistically analyzed. Results: High-concentrated colloids, red blood cells, and collagen fibers showed great SOS, while low-concentrated colloids, parathyroids, lymph follicles, and epithelial tissues including carcinomas demonstrated lower SOS. SAM clearly discriminated structure of thyroid components corresponding to low magnification of light microscopy. Thyroid tumors were classified into three groups by average SOS: the fast group consisted of follicular adenomas/carcinomas and malignant lymphomas; the slow group contained poorly differentiated/undifferentiated carcinomas; and the intermediate group comprised papillary/medullary carcinomas. Fragmented colloids, irregular-shaped follicles, and desmoplastic reactions were observed in the invasive area of surrounding carcinomas. Conclusion: The SAM imaging method had the following benefits: 1) precise images were acquired in a few minutes without special staining; 2) structural irregularity and desmoplastic reactions, which indicated malignancy, were detected; 3) images reflected tissue elasticity, which was statistically comparable among lesions by SOS; 4) follicular functional activity was predictable by converting colloid concentration to SOS; and 5) tumor classification was predictable by SOS because more poorly differentiated carcinomas had a tendency to show lower SOS. Keywords: scanning acoustic microscope, tissue elasticity, cancer imaging, thyroid tumor, parathyroid